PENGARUH KUALITAS PRODUK DAN REPUTASI TERHADAP KEPUTUSAN NASABAH MENGGUNAKAN JASA BANK SYARIAH INDONESIA - Bustomi Bustomi; Harya Kuncara Wiralaga; Siti Fatimah Zahra (Yayasan Education and Social Center, 2023)
This study aims to determine the effect of product quality and reputation on customer decisions to use the services of Bank Syariah Indonesia located in DKI Jakarta. The research method used is a survey method with a quantitative approach. The population in this study is customers of Bank Syariah Indonesia in DKI Jakarta. The sample of this study amounted to 272 respondents determined by the formula of the Isaac and Michael table because the population number is unknown. Data collection techniques using questionnaires. The data analysis technique used is multiple linear regression analysis. The results of this study show that, partially, product quality and reputation have a positive and significant influence on customer decisions